MENINGKATKAN EKONOMI KELUARGA MELALUI KREASI GARNISH SAYURAN DI GAMPONG DRIEN RAMPAK KECAMATAN JOHAN PAHLAWAN KABUPATEN ACEH BARAT - Leli Putri Ansari; Sri Rosmiati Sani; Yunidar Purnama Sari; Yayuk Eko Wahyuningsih; Mahdatun Nufus (Jurnal Pengabdian Agro and Marine Industry, 2023)
This community service activity carried out trough garnish creation training aims to provide skills to housewives to be skilled in creating vegetable garnishes as decorations to beautify food dishes which are usually used for tumpeng rice decoration, wedding food dish decoration, and hotel food dish decoration, café food dishes and also restaurant food decoration. If these housewives are proficient in making vegetable garnish creations, it will be an apportunity for entrepreneurship so that they can improve the family economy. The location of this community service activity is locatied in Gampong Drien Rampak RT. Neighborhood III Johan Pahlawan District, West Aceh Regency with a total of 19 participants. The implementation method used is training by delivering material through  lectures and practice. The results obtained from this training activity are that the women participants are very enthusiastic about participating in this training and it is hoped that the skills obtained from this vegetable garnish training activity will continue with entrepreneurship that can improve the family economy.